Takaful Retirement Annuity Plan in Malaysia: An Investigation on Consumers’ Perceived Value and Knowledge Mediated by Attitude - Morshed, Mohammad Niaz; Kabir, Sardar Md Humayun; Asuhaimi, Fadhilah Abdullah; Muhibbullah, Md (International Journal of Scientific Research and Management (IJSRM), 2020)
Annuities are being treated as a backup financial strategy throughout the age of retirement and a way of reducing the long-term risk of a person’s old age. Takaful markets in Malaysia have wanted to advance an annuity plan backed by Islamic Shari’ah and similar to the purpose pursued by an insurance company, but failed to do so after initiation in early 1999. The objective of this study was to investigate the relationship among consumers’ decision to take Takaful retirement annuity plan and their perceived value, knowledge mediated by attitude. Quantitative research has been conducted by a structured questionnaire survey on participants’ attitude, perceived value and knowledge of Takaful retirement annuity plan. The sample (n=121) for this study consisted of the employees working in different functional units of the International Islamic University Malaysia located in the metropolitan capital (Kuala Lumpur and Selangor) area of Malaysia. The findings from this study unveiled that the attitude and perceived value of the participants had a significant positive relationship with their decisions to take Takaful retirement annuity plan. But no direct connection has been found between knowledge and choices on Takaful retirement annuity plan. The significant practical implication of this study will be the Takaful operators, their customers, and researchers.